MENCETAK GENERASI QUR’ANI ANTI RADIKALISME MELALUI STRATEGI PEMBELAJARAN DI TAMAN PENDIDIKAN AL-QUR’AN (TPA) ROUDLOTUL MUBTADI’IN DESA MANCAR PETERONGAN JOMBANG - Mohamad Amin Mustofa; Ali Mahsun (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2020)
The TPQ strategy is a technique used by educational institutions in the process of communication between educators and students in printing the human heirs of the holy book of the Qur'an who can be good friends with the Koran who have the attitude / behavior of peace, tolerance and behavior. compassion based on the Pancasila ideology. Some of the focus of this problem as well as development include: 1. TPQ's strategy in creating anti-radicalism of the Qur'ani generation. 2. the supporting and inhibiting factors of the TPQ in creating the Qur'anic generation of anti-radicalism. The approach and type of research used is field research (field research) and is qualitative in nature. Data collection techniques using observation, interviews, and documentation. Data analysis techniques used data reduction, data display, drawing conclusions and verification. The technique of checking the validity of the data uses extended observations, increasing persistence / persistence, and triangulation. The results of the research on the TPQ Roudlotul Mubtadi'in Strategy in producing the anti-radicalism of the Qur'ani generation that were applied were the transinternalization strategy with the following steps: (1) the value transformation stage, namely the educator simply informing good and bad values to children through verbal or other communication, (2) the value transaction stage, namely the stage of carrying out two-way communication or reciprocal interaction between educators and students, (3) the transinternalization stage, namely the appearance of educators in front of children not only physically but his personality (personality). It can be concluded that the transinternalization strategy occurs in the communication of two personalities between educators and students who are actually involved.